Fortified Fluconazole Eyedrops for Treatment of Culvularia Corneal Ulcer - Muhammad Reza Arlas; Petty Purwanita (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2020)
Introduction: Fungal keratitis is less common than bacterial keratitis, generally representing less than 5%–10% of corneal infections in reported clinical series in the United States. But in developing countries (Ghana, India, China) it accounts for more than 90% of the cases. Corneal trauma by plant or vegetative material is the leading risk factor for fungal keratitis. One or more topical antifungals are usually administered with systemic support of oral antifungals. The most common classes of antifungal used for medical therapy include the polyenes, azoles, and the echinocandins. Case presentation: A 47-year-old male presented with a widening white patch on his left eye since 4 days before coming to our hospital. The left eye was injured by wood flakes 3 weeks ago. He felt a sore, red, watery left eye and blurred vision. He washed his eyes with betel leaf water. His left eye visual acuity was 1/60 and not improved with pinhole. There were blepharospasm, ciliary and conjunctival injection. Corneal examination showed a cloudy cornea, a central corneal defect sized 8x6 mm with an irregular margin, 2/3 to stromal depth, infiltrate, satellite lesion, and positive fluorescein staining at the defect margin. KOH examination demonstrated hyphae. The culture test of left corneal discharge identified a fungi species (Curvularia sp). We prescribed fortified fluconazole eye drops in combination with supportive therapy for 2.5 months. This regimen showed a significant increase in visual acuity to 6/30 with pinhole improvement of 6/21 in the left eye. Discussion: Imidazole acts by inhibiting ergosterol biosynthesis of the fungal cell wall, through action on the cytochrome P450-dependent enzyme. This leads to cell membrane destabilization and leakage. Curvularia sp belongs to the family of dematiaceous fungi. Its clinical manifestations include raised lesions and feathery edges; hypopyon rarely occurs, and the prognosis is quite good. Fluconazole (2 mg/ml) is available for injection and is a well-tolerated eye drop. The intravenous injection can be used as a topical treatment and can be given subconjunctivally at the same concentration. Conclusions: Fortified fluconazole eyedrops (2 mg/ml) can become an alternative and additional therapy for deep fungal keratitis, especially for Curvularia sp.